Lipid storage changes in human skeletal muscle during detraining - Zhu, Rong; Wen, Caiyun; Li, Jiance; Harris, M. Brennan; Liu, Yung-Yang; Kuo, Chia-Hua (Frontiers in Physiology, 2015)
Exercise training is known to increase intramuscular triglyceride content in both trained and untrained legs. The purpose of the study was to determine the changes of intramyocellular lipids (IMCL) and extramyocellular lipids (EMCL) of both trained and untrained legs during detraining. We measured both IMCL and EMCL levels in previously trained versus untrained legs during 4-weeks of detraining after 6-weeks of strength training. Eight young men (aged 21.4+/- 1.4 years) trained their vastus lateralis muscle in one leg using a dynamometer, whereas the contralateral leg served as untrained control. Muscle cross-sectional area (CSA), IMCL, EMCL, total creatine (creatine+phophocreatine) of extensor (vastus lateralis) muscles were assessed using magnetic resonance imaging (MRI) and proton magnetic resonance spectra (1H-MRS) before training, 3 days after and 28 days after the last bout of training. CSA was increased in both legs by Day 3 after training, and was still high at Day 28 post-training; IMCL increased in both legs by Day 3 after training, then decreased at Day 28 post-training only in the untrained leg; EMCL shows no significant change by Day 3 after training, but at Day 28 post-training has increased in the trained leg and decreased in the untrained leg; total creatine did not change significantly. Conclusion: Decreases of IMCL and EMCL storages in previously untrained leg during detraining indicates an ectopic influence on tissue lipid storage by different metabolic demand among tissues in the same human body.